Genetic Manipulation of Non-Falciparum Human Malaria Parasites - Vieira, Taís Baruel; Astro, Thafne Plastina; Moraes Barros, Roberto Rudge de (Frontiers in Cellular and Infection Microbiology, 2021)
The development of genetic manipulation of Plasmodium falciparum in the 1980s was key to study malaria biology. Genetically modified parasites have been used to study several aspects of the disease, such as red blood cell invasion, drug resistance mechanisms, gametocyte development and mosquito transmission. However, biological and genetic differences between P. falciparum and the other human malaria parasites make P. falciparum a poor model to study different species. The lack of robust systems of long-term in vitro culture of P. vivax and the other human malaria parasites lagged the genetic manipulation of these species. Here we review the efforts to generate genetically modified non-falciparum human malaria parasites, in vivo and in vitro. Using in vivo models – infection of non-human primates such as rhesus macaques and saimiri monkeys – researchers were able to generate transgenic lines of P. knowlesi, P. cynomolgi, and P. vivax. The development of long-term in vitro culture of P. knowlesi in the 2000’s, using rhesus and human red blood cells, created a platform to genetically manipulate non-falciparum malaria parasites. Recently, the use of CRISPR/Cas9 technology to genome edit P. knowlesi provides another tool to non-falciparum malaria research, extending the possibilities and allowing researchers to study different aspects of the biology of these parasites and understand the differences between these species and P. falciparum.